2012
DOI: 10.25011/cim.v35i3.16589
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous versus intraperitoneal insulin for patients with diabetes mellitus on continuous ambulatory peritoneal dialysis: Meta-analysis of non-randomized clinical trials.

Abstract: Background: Diabetes mellitus is one of the leading causes of end stage renal disease. Use of intraperitoneal (IP) nsulin in diabetic patients on peritoneal dialysis (PD) can restore glucose control to near normal values. The safety and efficacy of this method is unclear. Methods: We performed a meta-analysis to study the safety and efficacy of IP insulin administration in diabetic patients on PD. The primary outcome measures is glycemic control: secondary outcome measures were plasma lipids, insulin dose re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 15 publications
(19 reference statements)
0
17
0
Order By: Relevance
“…These polymers have been used to encapsulate inter alia 83 lysozyme, recombinant human epidermal growth factor and luteinising hormone-releasing 84 hormone agonist, leading to improvement of pharmacokinetic profiles and minimising 85 frequency of administration (8,9). They are generally fabricated using emulsion solvent superior to that seen following treatment with conventional SC insulin (19). However, the 120 approach is not without its clinical difficulties and more data is needed to assess long-term 121 safety, which will include evaluation of novel delivery strategies, such as nanoparticulate 122 platforms (19).…”
mentioning
confidence: 99%
“…These polymers have been used to encapsulate inter alia 83 lysozyme, recombinant human epidermal growth factor and luteinising hormone-releasing 84 hormone agonist, leading to improvement of pharmacokinetic profiles and minimising 85 frequency of administration (8,9). They are generally fabricated using emulsion solvent superior to that seen following treatment with conventional SC insulin (19). However, the 120 approach is not without its clinical difficulties and more data is needed to assess long-term 121 safety, which will include evaluation of novel delivery strategies, such as nanoparticulate 122 platforms (19).…”
mentioning
confidence: 99%
“…17 There is no evidence to link contamination through the MP with the development of peritonitis, however, there is a need to perform this disinfection, since contamination may happen following handling. Other than antibiotics, 18 the most commonly used intraperitoneal medications are heparin 7 and insulin, 19 however, reports linking the association between peritonitis and MP manipulation are contradictory. Selgas et al 20 reported the occurrence of 4 times more…”
Section: Discussionmentioning
confidence: 99%
“…In a meta‐analysis studying the safety and efficacy of IP insulin administration, the insulin dose required was more than twofold higher in the IP treatment, but glycemic control measured by hemoglobin A1C was equal to or better than the control obtained by SC insulin 105 . Increased IP insulin requirements of two‐ to threefold have been confirmed in multiple studies 103,106‐108 .…”
Section: Dialysis Initiation and Modality Differencesmentioning
confidence: 96%
“…Some have advocated for the administration of insulin into an empty peritoneum to improve the efficacy of IP insulin, 111 but this procedure increases the number of times the peritoneal space is accessed which, in turn, increases the risk for peritonitis. Furthermore, the lipid profile appeared to be adversely affected, with decreased HDLs and increased triglycerides, potentially increasing cardiovascular risk 105,112,113 . The disadvantages of IP administration of insulin are many and include increased risk of peritonitis, 106,114 risk of development of hepatic subcapsular steatonecrosis, 115 malignant omentum syndrome, 116 and increased costs incurred from higher insulin doses.…”
Section: Dialysis Initiation and Modality Differencesmentioning
confidence: 99%